ICT to Promote E-Governance in Municipal Corporation Ludhiana - Sharda, Dinesh; Taniya (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
The use of ICT in government has set the stage for greater transparency and the possibility for greater citizen participation. ICT such as Internet, GSM system, Computer and Online tools for effective information and communication service delivery should be made available in the local government area. The term e-governance focuses on the use of new ICT by governments as applied the full range of government functions. ICT acts in speeding up the flow of information and knowledge between government and citizen and transforming the way in which government and citizen interact. ICT holds particular promise in areas of governance and public participation. Open government and e-government proponents believe government in the digital age can use information to reduce corruption and increase government transparency, accountability, efficiency and citizen participation. Municipal Corporation Ludhiana aims to introduce automation and governance through ICT and GIS to simplify and improve service delivery, provide better information management and ensure citizen participation in governance.
Keywords: ICT; E-Governance; municipal corporation; local government